PENGARUH DISIPLIN KERJA DAN KAPABILITAS INDIVIDU TERHADAP KINERJA PEGAWAI DENGAN KEPUASAN KERJA SEBAGAI VARIABEL MEDIASI (Survei pada Pegawai Kantor Pelayanan Pajak Pratama Surakarta) - Mira Novita Sari, Marjam Desma Rahadhini & Sunarso (Universitas Slamet Riyadi, 2018)
research aims to analyze the significance of the influence of the discipline of work and individual capabilities against the job satisfaction on Tax Services Office employees Pratama Surakarta. To analyze the significance of the influence of the working discipline, individual capability and the Pontifical work against the performance Tax Services Office employee of Pratama Surakarta. To analyze job satisfaction in the mediated influence of discipline of work and individual capabilities against the performance Tax Services Office employee of Pratama Surakarta. This study used a survey method, the type of data the data used was qualitative and quantitative data. Population and sample in this research is all Tax Services Office employees Pratama Surakarta in particular section Supervisor and consulting (Waskon) as many as 50 employees. Technique of data analysis used the test of validity, reliability test, test the assumptions of classical, path analysis, t-test, F-test and coefficient of determination. The research results obtained the conclusion that: the discipline of work and capabilities of individual positive and significant effect against the job satisfaction. Disciplined work, individual capability and influential job satisfaction significantly to the performance of the employees. Job satisfaction mediate the influence of discipline of work and individual capabilities against the performance of employees.Keywords: disciplined work, individual capabilities, of the pontifical work, the performance of employees.